Influence of Integrated Nutrient Management on Fodder Pearl Millet in Transitional Plain of Luni Basin - Arjun Lal Bijarnia; Ummed Singh; Ramdev Sutaliya (International Journal of Economic Plants)
The field experiment was carried out in loamy sand soil at Agricultural Research Station, Keshwana (Jalore) during Kharif season 2018 with the specific objective to find out the influence of integrated nutrient management on fodder pearl millet. The experimental treatment consisted of seven treatments viz., 100% of RDF, 5 t FYM+50% of RDF, 5 t FYM+75% of RDF, 5 t FYM+100% of RDF, 5 t FYM+50% of RDF+ Biofertilizer and 5 t FYM+75% of RDF+ Biofertilizer laid out in randomized block design and replicated thrice. Application of 5 t FYM+100% RDF substantially improved plant height (149 cm), number of tillers per plant (4.52), green fodder yield (14.47 t ha-1) and dry fodder yield (2.38 t ha-1) over control. Similarly, application of 5 t FYM+100% RDF markedly fetched higher gross return (Rs. 28,940), net return (Rs. 9,856) and B:C ratio (1.52) over control and other treatments tested under the study. Efficient integrated nutrient management strategies are the potential approaches for improving green and dry fodder yield of fodder pearl millet and fetching higher returns in the Transitional Plain of Luni Basin (IIB) of Rajasthan. We concluded that applying integrated nutrient management having combination of organic and inorganic sources of nutrients would be worthwhile to improve fodder yield and achieving greater economic returns in fodder pearl millet.